The Effect of Instagram Influencers on Purchase Intentions Mediated by Brand Image on Cosmetic Products (Study on Gen Z Women): (Study on Gen Z Women) - Tamara, Dewi; Heriyati , Lidiya; Hanifa, Tsabita; Carmen , Michelle (Open Access Indonesia Journal of Social Sciences, 2021)
Rise of internet usage gives a sense of urgency for marketer to develop enchanted promotion methods through the help of social media. This research focuses on analyze the correlation between social media influencer and purchase intention with brand image as mediating variables. Object of this research is Generation Z women since their perspectives are rarely elaborated in previous research. Sample of this research is Generation Z women, actively using make-ups and skincare, and use Instagram in their daily basis. Validity is measured through convergent validity and discriminant validity, while reliability is measured through cronbach’s alpha and composite reliability. Hypotheses are measured using PLS-SEM and considered as significant if t-value > t-table. Results indicate that social media influencer significantly correlated with purchase intention when mediated with brand image. Specifically, numbers of followers, high-activity on social media, and influencer credibility influence brand image and purchase intention in significant ways. Moreover, positive brand image, public awareness, and brand uniqueness determined as mediating factors on the relationship social media influencer and purchase intention.